Pengaruh Pemberian Bahan Herbal Terfermentasi dengan Bioaktivator Lokal pada “Liquid Feed” Terhadap Konsumsi, Kecernaan Protein Kasar dan Energi pada Ternak Babi - Kase, Alexius N; Suryani, Ni Nengah; Aryanta, I Made S. (Yayasan Sumber Daya Manusia Cerdas, 2025)
The purpose of this study was to determine the effect of fermented herbal ingredients with local bioactivators on consumption, digestibility of crude protein and energy in pigs and also to determine the best level of fermented herbal ingredients in improving digestibility. The livestock used were 12 grower phase pigs aged 3-4 months with an initial body weight ranging from 34-43 kg with an average of 37 kg (CV = 4.12%). This study used a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications so that there were 12 experimental units. The treatments given were H0: liquid feed (basal ration + water 1: 2), H1: liquid feed + 10% fermented herbal (100ml / liter of water), H2: liquid feed + 15% fermented herbal (150 ml / liter of water) and H3: liquid feed + 20% fermented herbal (200 ml / liter of water). The variables studied were consumption, digestibility of crude protein and energy. The results showed that the treatment had a very significant effect (P<0.01) on consumption, digestibility of crude protein and energy. It was concluded that giving 10-20% fermented herbal ingredients increased consumption, digestibility of crude protein and energy. Giving 20% (200 ml/liter of water) fermented herbs with local bioactivators in liquid feed resulted in the best digestibility of crude protein and energy, namely (85.13% and 82.27%).